Plasticity of lumbosacral propriospinal neurons is associated with the development of autonomic dysreflexia after thoracic spinal cord transection - Hou, Shaoping (2008)
Complete thoracic (T) spinal cord injury (SCI) above the T6 level typically results in autonomic dysreflexia, an abnormal hypertensive condition commonly triggered by nociceptive stimuli below the level of SCI. Over-expression of nerve growth factor in the lumbosacral spinal cord induces profuse sprouting of nociceptive pelvic visceral afferent fibers that correlates with increased hypertension in response to noxious colorectal distension. After complete T4 SCI, we evaluated the plasticity of propriospinal neurons conveying visceral input rostrally to thoracic sympathetic preganglionic neurons. The anterograde tracer biotinylated dextran amine (BDA) was injected into the lumbosacral dorsal gray commissure (DGC) of injured/non-transected rats immediately after injury (acute) or 2 weeks later (delayed). At 1 or 2 weeks after delayed or acute injections, respectively, a higher density (p<0.05) of BDA(+) fibers was found in thoracic dorsal gray matter of injured versus non-transected spinal cords. For corroboration, fast blue (FB) or cholera toxin subunit beta (CTb) was injected into the T9 dorsal horns 2 weeks post-injury/non-transection. After 1 week transport, more retrogradely-labeled (p<0.05) DGC propriospinal neurons (T13-S1) were quantified in injured versus non-transected cords. We also monitored immediate early gene, c-fos, expression following colorectal distension and found increased (p<0.01) c-Fos(+) cell numbers throughout the DGC after injury. Collectively, these results imply that, in conjunction with local primary afferent fiber plasticity, injury-induced sprouting of DGC neurons may be a key constituent in relaying visceral sensory input to sympathetic preganglionic neurons that elicit autonomic dysreflexia after high thoracic SCI.